2011
DOI: 10.12698/cpre.2011.rr68
|View full text |Cite
|
Sign up to set email alerts
|

Learning Trajectories in Mathematics: A Foundation for Standards, Curriculum, Assessment, and Instruction

Abstract: Learning Trajectories in Mathematics: A Foundation for Standards, Curriculum, Assessment, and Instruction aims to provide:• A useful introduction to current work and thinking about learning trajectories for mathematics education • An explanation for why we should care about these questions • A strategy for how to think about what is being attempted in the field, casting some light on the varying, and perhaps confusing, ways in which the terms trajectory, progression, learning, teaching, and so on, are being us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
96
0
7

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 111 publications
(103 citation statements)
references
References 29 publications
0
96
0
7
Order By: Relevance
“…Working groups of experts in those two fields produced reports that concluded that there was empirical and theoretical support for the idea that the ways children learn some of the concepts and practices of science and mathematics could be characterized as typically advancing through identifiable levels or steps of growing understanding and skill (see Daro, Mosher, & Corcoran, 2011;Corcoran, Mosher, & Rogat, 2009). There also was support for the notion that children typically encounter identifiable difficulties or problems along the way which may hinder their movement from level to level on the progression.…”
Section: Resultsmentioning
confidence: 99%
“…Working groups of experts in those two fields produced reports that concluded that there was empirical and theoretical support for the idea that the ways children learn some of the concepts and practices of science and mathematics could be characterized as typically advancing through identifiable levels or steps of growing understanding and skill (see Daro, Mosher, & Corcoran, 2011;Corcoran, Mosher, & Rogat, 2009). There also was support for the notion that children typically encounter identifiable difficulties or problems along the way which may hinder their movement from level to level on the progression.…”
Section: Resultsmentioning
confidence: 99%
“…En este sentido, la información sobre una trayectoria de aprendizaje, entendida como contenido a ser aprendido por los estudiantes para maestro, puede ser usada como un instrumento conceptual para comprender y tratar situaciones de enseñanza y aprendizaje de las matemáticas (Llinares, 2004). Aprender a usar la información sobre las trayectorias de aprendizaje como un instrumento conceptual para desarrollar la competencia "mirar profesionalmente" el pensamiento matemático de los estudiantes, puede interpretarse en términos de su "instrumentalización" (entendido como el desarrollo de la capacidad del estudiante para maestro de usar la trayectoria de aprendizaje para interpretar la comprensión de los alumnos y tomar las correspondientes decisiones instruccionales que favorezcan su aprendizaje) (Daro, Mosher y Corcoran, 2011;. El análisis de este proceso de instrumentalización aporta información sobre la manera en la que los estudiantes para maestro aprenden a usar el conocimiento de matemáticas y sobre el aprendizaje de las matemáticas para apoyar sus decisiones en la enseñanza.…”
Section: Marco Teóricounclassified
“…As a result of these deliberations, CCII produced two reports, one for science and one for mathematics (Corcoran, Mosher, & Rogat, 2009;Daro, Mosher, & Corcoran, 2011). This policy brief reviews their conclusions and the implications of their findings for policy and for future research and development.…”
Section: Learning Progressions Proposed As a Tool For Supporting Adapmentioning
confidence: 99%